Exploring the therapeutic potential of mitochondrial uncouplers in cancer - Riya Shrestha; Edward Johnson; Frances L. Byrne (Elsevier, 2021)
Background: Mitochondrial uncouplers are well-known for their ability to treat a myriad of metabolic diseases, including obesity and fatty liver diseases. However, for many years now, mitochondrial uncouplers have also been evaluated in diverse models of cancer in vitro and in vivo. Furthermore, some mitochondrial uncouplers are now in clinical trials for cancer, although none have yet been approved for the treatment of cancer. Scope of Review: In this review we summarise published studies in which mitochondrial uncouplers have been investigated as an anti-cancer therapy in preclinical models. In many cases, mitochondrial uncouplers show strong anti-cancer effects both as single agents, and in combination therapies, and some are more toxic to cancer cells than normal cells. Furthermore, the mitochondrial uncoupling mechanism of action in cancer cells has been described in detail, with consistencies and inconsistencies between different structural classes of uncouplers. For example, many mitochondrial uncouplers decrease ATP levels and disrupt key metabolic signalling pathways such as AMPK/mTOR but have different effects on reactive oxygen species (ROS) production. Many of these effects oppose aberrant phenotypes common in cancer cells that ultimately result in cell death. We also highlight several gaps in knowledge that need to be addressed before we have a clear direction and strategy for applying mitochondrial uncouplers as anti-cancer agents. Major conclusions: There is a large body of evidence supporting the therapeutic use of mitochondrial uncouplers to treat cancer. However, the long-term safety of some uncouplers remains in question and it will be critical to identify which patients and cancer types would benefit most from these agents.